On the Theoretical Analysis of the Plant Propagation Algorithms. (21st March 2018) - Sulaiman, Muhammad; Salhi, Abdellah; Khan, Asfandyar; Muhammad, Shakoor; Khan, Wali
Abstract : Plant Propagation Algorithms (PPA) are powerful and flexible solvers for optimisation problems. They are nature-inspired heuristics which can be applied to any optimisation/search problem. There is a growing body of research, mainly experimental, on PPA in the literature. Little, however, has been done on the theoretical front. Given the prominence this algorithm is gaining in terms of performance on benchmark problems as well as practical ones, some theoretical insight into its convergence is needed. The current paper is aimed at fulfilling this by providing a sketch for a global convergence analysis.